МИЛЛИЙ ТӘРБИЯ - МӘНАЎИЙ ҚӘДИРИЯТЛАР ДЕРЕГИ - Назарбаев, Ф. (FAN va JAMIYAT, 2017)
The article deals with the issues of national-spiritual education of young generation and national-cultural heritage. It contains the ideas of the great thinkers of Central Asia about national values and moral.